Anesthesia in Renal Transplant - Kurniawaty, Juni; Ancilla, Cornelia; Arovah, Novita Intan (Jurnal Komplikasi Anestesi, 2022)
Background: Transplantation provides near-normal life and excellent rehabilitation compared to dialysis and is the preferred method of treating end-stage renal disease (ESRD) patients. Methods: We conducted a retrospective analysis of anesthesia management from 20 cases of live renal transplants carried out between August 2017 and April 2019 at Dr. Sardjito Central General Hospital, Yogyakarta. The subjects ' preoperative patient status, anesthesia management, and postoperative care were assessed. Results: Most patients had preoperative anemia, normal serum potassium, serum creatinine, and average ejection fraction. Anesthesia management began 24 hours before surgery, in which the patients were hospitalized, had peripheral IV access and fluid maintenance, and hemodialysis, followed by premedication 1 hour before surgery. Before surgery, anesthesia induction and intubation were done, followed by maintenance of anesthesia and intraoperative monitoring. Postoperative care consisted of the administration of analgesia and management of complications. Conclusion: Optimization of preoperative status, proper anesthesia management, and good postoperative care are keys to a successful renal transplant program.